Auditoría de gestión en la empresa OLEORÍOS S.A. y su incidencia en la toma de decisiones período 2013 - Chávez Vega, Lilian Yolanda (2015)
This audit work was conducted at the company OLEORÍOS SA whose manager is Mr. Juan Carlos Veloz, located on the grounds the Guinean Km 23 via Quevedo Windows.; dedicated to the processing of oil palm fresh fruit; with the main objective conducting an audit needed to demonstrate the impact on decision-making during the period 2013; which they were raised for specific objectives determine the degree of reliability and risk level, measure the efficiency and effectiveness of operations of the company and issue a final report using the analytical, inductive, deductive and systemic methods, in addition to the implementation of internal control by the components of COSO I, the surveys for the staff working in the company allowed to establish a level of trust and high risk; through the analysis of financial indicators, a gap of 20% in efficiency and 5% efficacy was detected; once the audit findings are four default on the purchase of palm oil, poor control of production, breach of risk policies, poor communication was evident; which significantly influence the process of decision making of the company. With the above specifications proceeded to make the final audit report and appropriate recommendations to the company activities; which they are suggested implementations are following a strict control to enable better decision-making at both the administrative and operational levels OLEORÍOS Company SA